PENGARUH LIQUIDITY, EARNINGS MANAGEMENT, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Jovinca Erdiana; Kartina Natalylova (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to obtain empirical evidence about several factors that influence the value of nonfinancial companies listed in the Indonesia Stock Exchange (BEI). This study aims to determine whether institutional ownership, profitability, liquidity, dividend policy, debt policy, earnings management, and free cash flow affect firm value. Data for this study was acquired from the financial statements of the nonfinancial companies listed in the Indonesia Stock Exchange over the past three years period 2019—2021. The sample in this study is 109 companies and was selected with the purposive sampling method. The multiple regression method is used to analyze the sample compiled. The result of this study shows that profitability and debt policy have a positive significant effect on firm value. This indicates that the company’s ability to obtain high profits and utilize its debt correctly to expand its business will increase the value of the firm. Meanwhile, institutional ownership, liquidity, dividend policy, earnings management, and free cash flow have no effect on firm value.